Effectiveness of understanding the post-operative instructions with respect to extraction of teeth in rural population through verbal, written and audio-visual aids. (Bangladesh Journal of Medical Science, 2024)
Aim: To compare the efficacy between verbal, written & audio-visual modes of communication in relation to post-operative instructions after extraction of teeth.Materials & Methods: Ninety patients were equally divided into three groups. Group 1 were given verbal instructions, Group 2 in written format and Group 3- Audio visual mode. Their responses were recorded using a standard questionnaire after 24 hours of extraction and subjected to statistical analysis.Results: Significant differences (p